Frequency of Malignancy in Asymptomatic Unilateral Enlarged Tonsil - TallatNajeeb, RizwanUllahChattah (Journal of Rawalpindi Medical College, 2013)
Background: To determine frequency of malignancy in unilateral enlarged tonsil (UET) in different age groups without any other clinical feature. Method: In this descriptive cross sectional study patients (n=70) who underwent tonsillectomy,for tonsil asymmetry, were included. Group I, patients were of 3-12 years and in group II, were of 13 and above.All the patients were assessed clinically for regional(otolaryngology) and systemic disease. After tonsillectomy, difference in tonsils size was recorded on gross pathology, then specimens were sent for histopathology. Results: In group I, 40 patients were of age 3 to 12 years. Clinically mild difference (+1) was noticed in 13(32%), moderate (+2) in 20 and marked in 7(17.5%). In gross pathology after tonsillectomy, no difference was noticed in +1 cases (0%), only in 13 (32%) in +2 and in 6 (15%) in +3, average was(19/40, 47.5%).Histopathology was either normal histology or reactive hyperplasia. None of tonsil revealed any type of malignancy.In group II 30 patients were of 13-56 years of age. Mild difference (+1) was in 5(16.66%),moderate (+2) was in 19(63.3%) and marked was in 20(66.6%).In gross pathology no difference in both tonsils in +1(<5mm), 5-10 mm difference was noticed in +2 and >10mm difference was noticed in +3 in all cases. Average was 83.3 %( 25/30).Histopathology was unremarkable except in one, B cell lymphoma. Average was 3.3% (1/30). Conclusion: In unilateral enlarged tonsils, no malignancy was found in paediatric group, while in adult group one patient showed malignancy (Lymphoma).